PENGARUH MEDIA TRANSGO TERHADAP PEMAHAMAN KONSEP TRANSFORMASI GEOMETRI PADA SISWA SMP - Hari Wahyuni, Isti; Fajariyah, Linda; Lausandi, Yosua; Nurwiani, Nurwiani; Maf'ulah, Syarifatul (TRANSFORMASI, 2024)
This research was motivated by problems in the field regarding the difficulties of junior high school students in understanding geometric transformation material. This research was carried out at Bhara Widya Catholic Middle School Lumajang in accordance with the results of observations which showed that learning media had never been used to instill the concept of geometric transformation. The aim of this research is to determine the influence of using Transgo media on understanding the concept of geometric transformation in class IX students at the school. This research is an experimental type of research with a quantitative design, posttest only control design. The instrument used was a comprehension test and the data was analyzed using inferential statistics. The results of the research show that there is a positive effect of using Transgo media on understanding the concept of geometric transformation in class IX students at Bhara Widya Catholic Middle School, which is known through the Asymp.Sig (2-tailed) value of 0.000 < 0.05 with an influence of 28.87% (more than 20%). Transgo media can be implemented in learning in other locations to increase students' understanding of geometric transformation material.